TUAN GURU H.M. SAID AMIN BIMA: ULAMA LOKAL DALAM JARINGAN SANAD HADIS - Muhammad Mutawali (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
The history records that the ulama played an important role for the development of Islam in the Nusantara, and even played an active role in the Indonesian independence process. They are the best sons of the nation who take Islamic scholarship directly at the center of the decline of Islamic doctrine. In the field of hadith (sanad & ijazah), the ulama Nusantara take an important position as ulama / teacher of hadith, so that some of them become mahaguru of the claimants of hadith knowledge from all country of the world and immediately give a ijazah. It aims to maintain the authenticity of the sanad and matan of hadis that originate from the Rasulullah oral remit from the forgery of hadith.The study of local ulama in the process of transmitting hadis in Indonesia, especially in eastern Indonesia, is very rarely found in the literature. Therefore, this study becomes important to be raised in a paper as a discourse, and also to fill the gap.This article will examine one of the Tuan Guru as a local ulama from Bima who was connected to the ulama network in the twentieth century and is also one of the local ulama who inherited the tradition of narration of traditions.